Currículo formal e informal e situações interpessoais como condições que afetam a autoavaliação sobre habilidades sociais e competência social de estudantes de Psicologia - Moraes, Patricia El Horr de (2020)
The interest in researching the variables of Psychology courses is justified by the number of higher education courses registered in Brazil, responsible for more than 300 thousand psychologists currently active. Of these variables, research on professional identity and social representation of Psychology stands out, which point out the relevance of the personal and interpersonal aspects of the professional psychologist. Among these aspects are social skills and social competence, whose studies aimed at training in Psychology enabled the characterization of students in this course and the knowledge about how teaching conditions can help the development of these behaviors. Considering these findings, the present study aimed to identify relationships between social skills, social competence, academic experiences and formal curriculum, based on the self-assessment of Psychology students. The study included 150 undergraduate psychology students from the first (87) and fifth year (63) of a Psychology course who responded to: (i) an adapted version of the Social Skills Inventory 2 (IHS2-Del Prette - which included a prospective assessment for first year students and retrospective assessment for fifth year students); (ii) a reduced version of the Academic Experience Questionnaire (QVA-r); (iii) a Social Competence Questionnaire in the Academic Context; (iv) a Questionnaire on teaching conditions involving Social Skills. The last two elaborated for this research.In addition to descriptive statistics, the data was analysed using group comparison analysis (t test) and correlation (Sperman's p). Content analysis was performed for qualitative data, which also underwent analysis of the statistical software IRaMuTeQ. Most of the participants had the repertoire of social skills classified as highly developed, and the fifth year students had statistically higher averages than the first year students. Prospective assessments showed that first-year students have expectations for the development of social skills that do not match the reality found in Psychology courses, while the retrospective assessment showed that graduating students perceived themselves with improved repertoire of social skills when compared to themselves in previous evaluation, according to statistical analysis that showed a significance index. Most formal teaching conditions seem to be unrelated to the respondents' social skills repertoire, with the exception of knowledge of the term “social skills” and participation in a practical course on this topic. In addition, many of the academic experiences correlated with social skills. The qualitative analysis showed several points of congruence with socially competent performances in students and raised a reflection on the relationships established in the Psychology course. The results suggest that the academic experiences specific to Psychology courses and practical social skills courses are related to the development of these behaviors, while evidencing the need to promote formal conditions that focus on social behaviors.